2012
DOI: 10.1007/s11684-013-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

A case of thymic Langerhans cell histiocytosis with diabetes insipidus as the first presentation

Abstract: Langerhans cell histiocytosis (LCH) is an idiopathic group of reactive proliferative diseases linked to aberrant immunity, pathologically characterized by clonal proliferation of Langerhans cells. LCH rarely involves the thymus. We report a case of thymic LCH with diabetes insipidus as the first presentation, without evidence of myasthenia gravis and without evidenced involvement of the skin, liver, spleen, bones, lungs and superficial lymph nodes. This present case may have important clinical implications. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In this study, patients diagnosed with LCH were divided into 2 groups—SS and MS groups, and those in the latter group presenting with nonspecific symptoms made it challenging to diagnose. 10,11 In the present study, longest duration from presentation to diagnosis was noted in patients with symptoms related to bony lesions. On the other hand, patients in the MS group deteriorated rapidly that led to earlier evaluation and diagnosis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In this study, patients diagnosed with LCH were divided into 2 groups—SS and MS groups, and those in the latter group presenting with nonspecific symptoms made it challenging to diagnose. 10,11 In the present study, longest duration from presentation to diagnosis was noted in patients with symptoms related to bony lesions. On the other hand, patients in the MS group deteriorated rapidly that led to earlier evaluation and diagnosis.…”
Section: Discussionsupporting
confidence: 50%
“…LCH patients presenting with central DI have been reported. 11 In our study, there was 1 patient who presented with polydipsia due to central DI secondary to painless skull lesions.…”
Section: Discussionmentioning
confidence: 63%
“…Involvement in MS LCH represents the largest group of thymic LCH characterized in the literature. However, although our review identified numerous reported cases of thymic involvement in the context of MS LCH (Supplemental Table 1; http://dx.doi.org/10.2350/15-01-1593-OA.S1), only 11 cases [1012,1417,37] and our 2 consult cases (Table 3) had ancillary confirmation of LCH in the thymus. Of note, a case of a fibrosing mediastinitis in the context of bone LCH may represent a “burnt-out” type LCH pattern with the absence of LCH cells in the thymus (CD1a- and S100-) with a fibrotic background; however, for the purposes of this study, that case was not included in the cohort [18].…”
Section: Resultsmentioning
confidence: 85%
“…Two newer studies [9,10] support the notion that thymic involvement of multisystem (MS) LCH occurs at a younger age (0.7-2 years) and is associated with skin and high-risk involvement (ie, bone marrow, liver, spleen), along with higher rates of reactivation and mortality [10], Both of these studies and isolated case reports highlight the importance of thymic involvement in MS LCH disease. However, there is little description in the literature [10][11][12][13][14][15][16][17][18][19] of the pathologic patterns of thymic involvement in the context of Langerhans cell proliferations and LCH disease.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrinologic manifestations of LCH are known to involve primarily the hypothalamic-pituitary region, with the clinical hallmark of DI 8,9 . DI has been an acknowledged manifestation of LCH for almost 30 years and can be revelatory for LCH and other severe conditions in children 5,8, [10][11][12] . Diff erential diagnosis of the causes includes germinoma, craniopharyngioma, LCH, local infl ammatory, autoimmune, and vascular diseases, trauma, sarcoidosis, metastases, and cranial malformations, among which LCH is one of the most common 13 .…”
Section: Case Reportmentioning
confidence: 99%